Design and properties of 100% waste-based ternary alkali-activated mortars: Blast furnace slag, olive-stone biomass ash and rice husk ash. (10th January 2020) - Font, Alba; Soriano, Lourdes; de Moraes Pinheiro, Sayonara Maria; Tashima, Mauro M.; Monzó, José; Borrachero, Maria Victoria; Payá, Jordi
Abstract: Alkali-activated cements (AACs) technology is being widely investigated as a replacement for ordinary Portland cement (OPC) for environmental benefits. Blast furnace slag (BFS) is one of the most well known precursors used in AACs, having comparable properties to those of traditional OPC-based materials. AACs require alkali solutions, which are commonly based on a combination of sodium or potassium hydroxides with sodium or potassium silicates in high concentration. These alkali solutions represent the use of chemical reagents, and thus can have major environmental, health and economic impacts. Olive-stone (also known as olive pits) biomass ash (OBA) is a residue mainly composed of calcium and potassium oxides. Rice husk ash (RHA) is a rich silica residue from the combustion of rice husk. The combination of both residues can produce a good activating reagent for BFS-based AACs. In the present work, 100% waste-based ternary alkali-activated mortars (TAAM) based on BFS activated by OBA and RHA were developed. The mortars were assessed in terms of their dosage, curing treatment and time evolution. Finally an eco-friendly 100% waste-based TAAM with 67.39 ± 0.44 MPa after 90 days of curing at 20 °C is obtained and a complete microstructural characterization shows a dense and compact matrix with binding gel products labelled as C(K)–S(A)-H and C(K)–S–H. Highlights: 100% waste-based ternary alkali-activated mortars were successfully developed. Blast furnace slag (BFS) was activated by means a mixture of biomass derived ashes. Biomass derived ashes (from Olive-stone, OBA, and from rice husk ash, RHA) were employed. The ternary BFS/OBA/RHA systems yielded mortars with strength in the range 40–70 MPa.